Method for roll-to-roll continuous preparation of pre-lithiation Si-based negative electrode with rich LiF-SEI film

Through the continuous roll-to-roll preparation method, fluorine-containing electrolyte is sprayed and contact prelithiation is used to form a LiF-SEI-rich film, which solves the volume expansion and cycle stability of silicon-based anode materials in lithium-ion batteries, and achieves efficient and environmentally friendly battery prelithiation and cycle performance improvement.

CN119943878APending Publication Date: 2025-05-06HENAN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510269842.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

The application of silicon-based anode materials in lithium-ion batteries is limited by problems such as volume expansion, low inherent conductivity and low Li+ diffusion rate, resulting in a decrease in cycle stability and life.

Method used

The continuous roll-to-roll preparation method is adopted, and the contact prelithiation of fluorine-containing electrolyte is sprayed and ultra-thin lithium tape is used for contact prelithiation to form a LiF-SEI-rich film, which optimizes the "closing time" of the Li+ solvation structure and the electron/Li+ transmission channel.

Benefits of technology

It improves the cycle stability and prelithiation efficiency of SiC negative electrode, extends the cycle life of the battery, and improves mechanical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119943878A_ABST
    Figure CN119943878A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a method for roll-to-roll continuous preparation of a pre-lithiation Si-based negative electrode with a LiF-SEI-rich film, and the method comprises the following steps: (1) spraying fluorine-containing electrolyte on the upper and lower surfaces of a Si-based negative electrode belt; (2) pulling two ultrathin lithium strips and the Si-based negative electrode strip with the two surfaces coated with the fluorine-containing electrolyte to pass through a roll-to-roll pre-lithiation device, and rolling the two ultrathin lithium strips and the Si-based negative electrode strip; and (3) removing the ultrathin lithium strips on the two sides of the Si-based negative electrode strip, and drying the Si-based negative electrode strip to obtain the pre-lithiated Si-based negative electrode rich in the LiF-SEI film. According to the present invention, the high-stability and thin SEI film construction and the pre-lithiation efficiency improvement are achieved, and the pre-lithiation SiC negative electrode rich in the LiF-SEI film has the high mechanical property, can be used for the continuous pre-lithiation of the Si-based negative electrode and the construction of the SEI film on the electrode surface so as to improve the cycle performance, has advantages of high efficiency, environmental protection and no need of the complex equipment, and has the high compatibility with the existing battery manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a method for continuously preparing a pre-lithiated Si-based negative electrode having a LiF-SEI-rich film by roll-to-roll continuous preparation. Background Art

[0002] Silicon-based anode materials have high natural abundance, good environmental friendliness, and relatively low lithium insertion potential (<0.4V vs Li / Li + ) and high theoretical specific capacity (4200mA·h / g), it is considered to be one of the most promising negative electrode materials for the next generation of LIBs (Lithium-Ion Batteries). Unfortunately, the huge volume expansion (up to 300-400%) and low intrinsic conductivity (10 -5 Up to 10 -3 S / cm) and low Li + Diffusion rate (10 -14 Up to 10 -13 cm 2 / s) seriously hinders its industrial development. At present, strategies such as nano-sizing, coating, doping and composite can effectively construct a three-dimensional conductive network and reserve buffer space to a certain extent, improving the cycle stability of silicon-based negative electrodes. However, silicon-based negative electrodes consume a large amount of active Li in the positive electrode or electrolyte inside the full battery. + , forming SEI film (Solid Electrolyte Interface) and irreversible products, reducing ICE (Initial Coulombic Efficiency) and cycle performance.

[0003] Contact prelithiation strategy can provide additional active Li to LIBs + To improve ICE. Professor Zhang Qiang's team at Tsinghua University and collaborators successfully inserted Li-Ag alloy as a guiding artificial electron channel (AEC) layer for contact pre-lithiation into the Li source film / graphite negative electrode interface by combining magnetron sputtering and vacuum thermal evaporation. However, the equipment cost required for magnetron sputtering and vacuum thermal evaporation is relatively high, the operation steps are many and require precise metering, and the process is relatively difficult. Roll-to-roll lithium replenishment is a pre-lithiation method that can be produced continuously; the team of Professor Wu Hui and Professor Li Xiaoyan at Tsinghua University has developed a continuous electrodeposition transfer pre-lithiation technology based on a roll-to-roll device, which uses continuous electrodeposition to deposit lithium metal on the side of the current collector to obtain a pre-lithiation current collector, and then transfers the negative electrode active material (graphite) to the pre-lithiation current collector to obtain a pre-lithiation lithium-ion battery electrode, realizing the continuous and low-cost preparation of pre-lithiation negative electrodes.

[0004] However, only supplementation of Li +The SEI film formed cannot exist stably: (1) As the silicon anode repeatedly expands in volume, the SEI film breaks and the active Li is lost. + ; (2) During the cycle, Li + The embedding and extraction of silicon-based materials cause vacancies and pores to form inside the electrode material, causing the liquid electrolyte to penetrate into the Si particles, resulting in changes in the volume of the silicon negative electrode. The repeated volume changes of the silicon-based material make it difficult for it to achieve effective contact with the surrounding material components. The resulting stress changes will destroy the designed three-dimensional electronic / Li + Transmission channel and SEI film. An overly thick SEI film will also lead to the formation of dead Si, causing the battery cycle life to decline sharply. Therefore, the design of the SEI film is of great significance. Unfortunately, the SEI film constructed by the current contact pre-lithiation method is difficult to alleviate the volume expansion of the SiC negative electrode during the cycle, resulting in a sharp decline in the cycle life. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a roll-to-roll continuous preparation method for a pre-lithiated Si-based negative electrode with a LiF-rich SEI film, by designing a new weak solvation fluorine-containing electrolyte formula to accurately control the Li in the contact pre-lithiation process. + Solvation structure and electronic / Li + The transmission channel "closing time" enables the preparation of high cycle stability pre-lithiated SiC anode with LiF-rich SEI film.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A roll-to-roll continuous method for preparing a pre-lithiated Si-based negative electrode having a LiF-rich SEI film comprises the following steps:

[0008] (1) spraying a fluorine-containing electrolyte on the upper and lower surfaces of the Si-based negative electrode strip so that the fluorine-containing electrolyte can evenly infiltrate the electrode pores; the fluorine-containing electrolyte comprises a cyclic ether solvent and a fluorine-containing lithium salt, and the energy difference between the LUMO of the fluorine-containing lithium salt and the cyclic ether solvent is greater than 1.5 eV;

[0009] (2) pulling two ultra-thin lithium ribbons and a Si-based negative electrode ribbon sprayed with a fluorine-containing electrolyte on both sides through a roll-to-roll pre-lithiation device; the two ultra-thin lithium ribbons are respectively located on the upper and lower sides of the Si-based negative electrode ribbon, and the three are rolled through the roll-to-roll pre-lithiation device; after lithium ions are released from the ultra-thin lithium ribbons, they are embedded in the Si-based negative electrode ribbon through the electrolyte, and the electrochemical potential of the Si-based negative electrode ribbon decreases as the amount of embedded lithium increases, and the electrolyte is spontaneously reduced and decomposed on its surface to form an SEI film;

[0010] (3) removing the ultra-thin lithium strips on both sides of the Si-based negative electrode strip, drying the Si-based negative electrode strip, and obtaining a pre-lithiated Si-based negative electrode with a LiF-rich SEI film.

[0011] Furthermore, the cyclic ether solvent includes at least one of 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and methyltetrahydrofuran; the fluorine-containing lithium salt includes one or more of LiPF6, LiTFSI, LiPO2F2, LiFSI, and LiODFB.

[0012] Furthermore, other solvents of the fluorine-containing electrolyte include diluents or film-forming additives.

[0013] Furthermore, in the fluorine-containing electrolyte, the concentration of the fluorine-containing lithium salt is 0.1-2 mol / L.

[0014] Furthermore, in step (1), the amount of fluorine-containing electrolyte sprayed on the Si-based negative electrode tape is 500-2000 ml / m 2 , the spraying temperature is 10-30℃, and the environment is a water-free environment.

[0015] Furthermore, in step (2), the speed at which the ultra-thin lithium strip and the Si-based negative electrode strip pass through the roll-to-roll pre-lithiation device is 1-5 cm / s; the rolling temperature of the roll-to-roll pre-lithiation device during the rolling process is 10-30°C, the number of rolling times is 1-3 times, the rolling pressure is 10-100 KPa, and the relative humidity of the rolling environment is 10%-30%.

[0016] Furthermore, in step (3), the drying temperature of the Si-based negative electrode strip is 50-60°C, and the drying time is 0.5-2h; the used ultra-thin lithium strip is polished, cut, crushed, extruded, thinned and rolled by a lithium metal recovery device to expose the fresh surface for secondary utilization.

[0017] Furthermore, the Si-based negative electrode tape is a silicon-carbon composite material or a silicon-oxygen-carbon composite material; the surface capacity of the Si-based negative electrode tape is 2-5 mAh / cm 2 , with a thickness of 50-250 μm; the ultra-thin lithium strip has a thickness of 5-20 μm and is loaded on the surface of the copper strip.

[0018] Furthermore, the SEI film thickness of the pre-lithiated Si-based negative electrode having a LiF-rich SEI film is 10-100 nm.

[0019] The working principle of the present invention is to precisely control the Li + Solvation structure and electronic / Li + The transmission channel "closing time"; the contact pre-lithiation strategy is to pre-replenish lithium by bringing the lithium source into contact with the negative electrode before cycling, which can compensate the active Li for the SiC negative electrode before cycling +, and at the same time, the electrochemical potential (μA) of the electrode material is changed to make it react with the electrolyte components to form a LiF-rich SEI film.

[0020] The beneficial effects of the present invention are:

[0021] The present invention aims at the poor thermal stability of the solid-liquid interface of the SiC negative electrode and the active Li + In order to solve the problems of loss and so on, based on the competitive coordination mechanism and in-situ polymerization theory, the passivation process of SEI film is regulated by optimizing the structure of fluorine-containing electrolyte, so that LiF is formed before the decomposition of ether-based electrolyte solvent. At the same time, the present invention selects the components in the contact pre-lithiation electrolyte through in-situ polymerization theory to convert electron / Li + The closing time of the transmission path is reasonably controlled, and the elastic toughness of the organic matter in the SEI film and the density of LiF in the non-electrode component are controlled to achieve high stability, thin SEI film construction and improved pre-lithiation efficiency. The pre-lithiation SiC negative electrode rich in LiF-SEI film has high mechanical properties.

[0022] The present invention can be used for continuous pre-lithiation of Si-based negative electrodes and construction of SEI films on the electrode surfaces to improve cycle performance, has the advantages of high efficiency, environmental protection, and no need for complex equipment, and has high compatibility with existing battery manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0024] Figure 1 Schematic diagram of the pre-chemical process of an embodiment of the present invention.

[0025] Figure 2 Schematic diagram of the lithium metal recovery process according to an embodiment of the present invention.

[0026] Figure 3 The cycle performance data of button batteries assembled from the negative electrode sheets of Examples 1-6, Example 8, Example 10 and Comparative Example 1 of the present invention; wherein, (a) is the cycle performance of button batteries assembled from the negative electrode sheets of Comparative Example 1 and Examples 1-3; (b) is the cycle performance of button batteries assembled from the negative electrode sheets of Examples 4-6 and Example 10; (c) is the first charge and discharge curve of the button battery assembled from the negative electrode sheet of Example 8.

[0027] Figure 4 This is a SEM image of the negative electrode that has not been pre-lithiated in Verification Example 1 of the present invention.

[0028] Figure 5 This is a SEM image of the negative electrode of Example 1 of the present invention.

[0029] Figure 6 It is an X-ray photoelectron spectrum analysis diagram of the negative electrode in Example 1 of the present invention; wherein, (a) is an X-ray photoelectron spectrum analysis diagram of the pre-lithiation negative electrode in Example 1 after 10 cycles of charge and discharge test; (b) is an X-ray photoelectron spectrum analysis diagram of the pre-lithiation negative electrode in Example 1.

[0030] Figure 7 These are cross-sectional SEM images of the negative electrode of Verification Example 1 of the present invention; wherein, (a) is a cross-sectional SEM image of the non-pre-lithiated SiC electrode before cycling, (b) is a cross-sectional SEM image of the non-pre-lithiated SiC electrode after the first discharge, (c) is a cross-sectional SEM image of the non-pre-lithiated SiC electrode after the first charge, (d) is a cross-sectional SEM image of the pre-lithiated SiC electrode of Example 1 before cycling; (e) is a cross-sectional SEM image of the pre-lithiated SiC electrode of Example 1 after the first discharge; (f) is a cross-sectional SEM image of the pre-lithiated SiC electrode of Example 1 after the first charge.

[0031] Figure 8 The nanoindentation test results of the negative electrode of the non-pre-lithiation verification example 1 and the negative electrode of Example 1 of the present invention are shown.

[0032] Fig. 9 Comparison of the results of the three groups of tests in Verification Example 2 of the present invention; wherein, (a) is the first group of electrochemical test results; (b) is the second group of electrochemical test results; (c) is the third group of electrochemical test results. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0034] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0035] A roll-to-roll continuous method for preparing a pre-lithiated Si-based negative electrode having a LiF-rich SEI film comprises the following steps:

[0036] (1) spraying a fluorine-containing electrolyte on the upper and lower surfaces of the Si-based negative electrode strip 100 so that the fluorine-containing electrolyte can evenly infiltrate the electrode pores to improve the pre-lithiation efficiency;

[0037] (2) pulling two ultra-thin lithium ribbons 200 and a Si-based negative electrode ribbon 100 sprayed with a fluorine-containing electrolyte on both sides through a roll-to-roll pre-lithiation device 2; the two ultra-thin lithium ribbons 200 are respectively located on the upper and lower sides of the Si-based negative electrode ribbon 100, and the three are rolled by the roll-to-roll pre-lithiation device 2; the pre-lithiation efficiency is regulated by controlling the rolling intensity and the conveyor belt speed; during the rolling process, lithium ions are released from the ultra-thin lithium ribbon 200 and then embedded in the Si-based negative electrode ribbon 100 through the electrolyte, and the electrochemical potential of the Si-based negative electrode ribbon 100 decreases as the amount of embedded lithium increases, and the electrolyte is spontaneously reduced and decomposed on its surface to form a LiF-rich SEI film;

[0038] (3) removing the ultra-thin lithium strips 200 on both sides of the Si-based negative electrode strip 100, drying the Si-based negative electrode strip 100, and obtaining a pre-lithiated Si-based negative electrode with a LiF-SEI-rich film; the used ultra-thin lithium strip 200 is polished, cut, crushed, squeezed, pressed and rolled to expose a fresh surface for secondary use, thereby saving production costs; Figure 1 It is a schematic diagram of the pre-physicalization process of the present invention; Figure 2 Schematic diagram of the processing flow for secondary utilization of lithium metal after recovery.

[0039] The fluorine-containing electrolyte includes a cyclic ether solvent and a fluorine-containing lithium salt, and other solvents include a diluent or a film-forming additive; the energy difference between the LUMO of the fluorine-containing lithium salt and the cyclic ether solvent is greater than 1.5 eV; the cyclic ether solvent includes at least one of 1,3-dioxolane (DOL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), and methyltetrahydrofuran (MeTHF); the fluorine-containing lithium salt includes one or more of LiPF6 (lithium hexafluorophosphate), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiPO2F2 (lithium difluorophosphate), LiFSI (lithium bis(fluorosulfonyl)imide), and LiODFB (lithium difluorooxalatoborate).

[0040] Furthermore, in the fluorine-containing electrolyte, the solvent has a concentration of analytical grade or above, and the concentration of the fluorine-containing lithium salt is 0.1-2 mol / L.

[0041] Furthermore, in step (1), the fluorine-containing electrolyte is sprayed using an electrolyte spraying device 1 with a controllable flow rate and a spray head; the amount of the fluorine-containing electrolyte sprayed on the Si-based negative electrode tape 100 is 500-2000 ml / m 2 , the spraying temperature is 10-30℃, and the environment is a water-free environment.

[0042] Furthermore, in step (2), the roll-to-roll pre-lithiation device 2 includes a first composite roller 21 and a second composite roller 22 arranged opposite to each other in the upper and lower parts, and the ultra-thin lithium strip 200 and the Si-based negative electrode strip 100 move through the first composite roller 21 and the second composite roller 22 at a speed of 1-5 cm / s; the rolling temperature of the roll-to-roll pre-lithiation device 2 during the rolling process is 10-30°C, the number of rolling times is 1-3 times, the rolling pressure is 10-100 KPa, and the relative humidity of the rolling environment is 10%-30%. The roll-to-roll method of the present invention mainly provides a continuous pre-lithiation method, and the rolling pressure is mainly to enable the electrode and the lithium strip to be in continuous contact. After the fluorine-containing electrolyte is sprayed, the fluorine-containing electrolyte will infiltrate the surface and pores of the Si-based negative electrode strip 100, so the residual electrolyte in the roll-to-roll process is sufficient to decompose and form an SEI film (thickness is about 10-100 nm) later.

[0043] Furthermore, in step (3), the Si-based negative electrode strip 100 is dried by a drying device 3 at a drying temperature of 50-60°C for a drying time of 0.5-2h; the used ultra-thin lithium strip 200 is polished, cut, crushed, extruded, thinned and rolled by a lithium metal recovery device 4 to expose a fresh surface for secondary use; the ultra-thin lithium strip 200 has a thickness of 5-20 μm and is loaded on the surface of a copper strip, which provides a carrier to prevent the lithium metal from being easily broken or deformed; a layer of ultra-thin lithium strip 200 and a layer of copper strip are stacked and rolled into a roll, so that the two are tightly attached and passed through a roll-to-roll pre-lithiation device 2; during recycling, the copper strip is only retracted into a roll, and the ultra-thin lithium strip 200 is crushed and then recycled.

[0044] Furthermore, the Si-based negative electrode tape is a silicon-carbon composite material or a silicon-oxygen-carbon composite material; the surface capacity of the Si-based negative electrode tape is 2-5 mAh / cm 2 , thickness is 50-250μm.

[0045] Furthermore, the SEI film thickness of the pre-lithiated Si-based negative electrode having a LiF-rich SEI film is 10-100 nm.

[0046] The failure of SiC anodes is mainly attributed to: (1) the huge volume fluctuation of Si particles during the cycle, which leads to the poor solid-liquid interface stability of SiC anodes; (2) the + During the continuous embedding and extraction process, the vacancies generated will cause the spatial configuration of Si particles and SEI film to evolve from the classic "core-shell" structure to the "plum blossom pudding" structure, destroying the electron / Li + The transmission path and the formation of dead Si can be compensated by building a SEI film during the contact pre-lithiation process. + Loss and solving the problem of thermally fragile interface characteristics are effective means to achieve stable cycling and high capacity retention.

[0047] During the contact prelithiation reaction, Li + The electrons and ions enter the SiC particles from the ion channel (electrolyte adsorbed in the contact interface and pores) and the electron channel (the contact point between the Li metal and the negative electrode). The electrochemical potential of the SiC negative electrode decreases with the increase of the amount of lithium insertion, causing the electrolyte to spontaneously reduce and decompose on its surface to form a SEI film; until the SEI film reaches a certain thickness, the ion and electron channels are blocked, forcing the contact pre-lithiation reaction to terminate.

[0048] The process of the present invention mainly controls the fluorine-containing lithium salt and cyclic ether solvent with low LUMO energy to preferentially decompose to generate LiF, and then as the reaction proceeds, a polymer layer is formed to block the reaction. The SEI film is a mixed component of organic and inorganic; the fluorine-containing lithium salt provides the F element for forming the LiF-rich SEI film, and the LUMO energy difference between the ether solvent and the lithium salt in the fluorine-containing electrolyte can make the inorganic component easier to form; the cyclic ether solvent forms a polymer, which is conducive to forming a complete, high-strength and tough organic outer layer to protect the rich LiF inside the SEI film.

[0049] The present invention is based on the competitive reduction mechanism between electrolyte components and the in-situ polymerization theory. The passivation process of the SEI film is regulated by controlling the components of the fluorine-containing electrolyte, so that the fluorine-containing lithium salt is preferentially reduced and decomposed to form LiF at the negative electrode interface before the organic solvent decomposes, and a LiF-rich SEI film is formed on the negative electrode surface. The organic solvent polymerization is promoted by adding lithium salts to the fluorine-containing electrolyte to ensure that the mechanical properties of the SEI film are improved; if the lithium salts are not allowed to promote the polymerization of the organic solvent, the repeated expansion of the electrode in the later cycle will further cause the SEI to rupture, and the electrolyte and the electrode material will contact and decompose to form the SEI film. At the same time, the electron / Li ratio is controlled by changing the molecular weight of the organic polymer in the contact pre-lithiation electrolyte through in-situ polymerization. + The transmission path closing time changes the elastic toughness of the organic matter in the SEI film and the density of LiF in the non-polar component; the cyclic ether solvents such as tetrahydrofuran and 1,3-dioxolane (DOL) used in the present invention are all low-molecular-weight, the elastic toughness of the organic matter in the SEI film is better, and the formed SEI film is thinner, which is conducive to the rapid transmission of lithium ions, thereby improving the rate performance of the battery, and further realizing the construction of a high-stability, thin SEI film and improving the pre-lithiation efficiency, and preparing a pre-lithiation SiC negative electrode with a LiF-SEI film rich in high mechanical properties.

[0050] The roll-to-roll process is used in the production of electrode sheets. The present invention innovatively uses the roll-to-roll process for continuous pre-lithiation of double-sided electrodes, which has the advantages of high efficiency, environmentally friendly manufacturing, and no need for complex equipment, and has high compatibility with existing battery manufacturing; (2) The fluorinated lithium salt with low LUMO energy in the fluorinated electrolyte will form a LiF-rich SEI film before the high LUMO ether solvent decomposes, thereby improving the pre-lithiation efficiency and cycle stability.

[0051] Different from the roll-to-roll pre-lithiation method (referred to as transfer method) in the prior art in which the environment between rolls is dry, the transfer method directly transfers molten lithium or deposited lithium to the electrode surface, which only improves the pre-lithiation effect of the electrode. The present application adds electrolyte between the ultra-thin lithium strip and the electrode, thereby improving the pre-lithiation and constructing an SEI film on the electrode surface to improve the cycle performance.

[0052] Various examples and comparative examples are given below. Different lithium salts and ether-containing single (mixed) solvents are provided in different examples. In the examples and comparative examples, unless otherwise specified, the concentrations of the reagent solutions are all analytically pure or higher.

[0053] Example 1

[0054] A roll-to-roll continuous method for preparing a pre-lithiated Si-based negative electrode having a LiF-rich SEI film comprises the following steps:

[0055] (1) Spraying a fluorine-containing electrolyte on the upper and lower surfaces of a Si-based negative electrode tape so that the fluorine-containing electrolyte can evenly infiltrate the electrode pores; the Si-based negative electrode tape is composed of a silicon-carbon composite material (SiC), the thickness of the Si-based negative electrode tape is 80 μm, and the spraying amount of the fluorine-containing electrolyte is 700 ml / m 2 ;

[0056] (2) pulling two ultra-thin lithium strips and a Si-based negative electrode strip sprayed with a fluorine-containing electrolyte on both sides through a roll-to-roll pre-lithiation device; the two ultra-thin lithium strips are respectively located on the upper and lower sides of the Si-based negative electrode strip, and the two ultra-thin lithium strips are pulled by a reeling and unwinding mechanism, and the unwinding speed is the same as the traveling speed of the Si-based negative electrode strip, both of which are 2 cm / s; the three are rolled by the roll-to-roll pre-lithiation device, so that the two ultra-thin lithium strips are in contact with the upper and lower surfaces of the Si-based negative electrode strip, and lithium ions are released from the ultra-thin lithium strips and undergo a contact pre-lithiation reaction under the action of the fluorine-containing electrolyte, and the electrolyte is spontaneously reduced and decomposed on the surface of the Si-based negative electrode strip to form an SEI film; the rolling temperature is 30° C., the rolling number is 1 time, the rolling pressure is 20 KPa, and the relative humidity of the rolling environment is 15%; the thickness of the ultra-thin lithium strip is 10 μm;

[0057] (3) Remove the ultra-thin lithium strips on both sides of the Si-based negative electrode strip, dry the Si-based negative electrode strip, and finally obtain a pre-lithiated Si-based negative electrode with a LiF-SEI-rich film; note that the pre-lithiated Si-based negative electrode with a LiF-SEI-rich film cannot be rolled or stretched after obtaining it, so as not to damage the SEI film structure.

[0058] In this embodiment 1, the fluorine-containing electrolyte uses electronically pure tetrahydrofuran (THF) or higher as solvent, and the solute is LiPF6 powder; the fluorine-containing electrolyte is prepared by dissolving LiPF6 in THF solvent to prepare a 0.1M LiPF6 solution. The pre-lithiated Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 0.1M LPF-THF. The energy difference between the LUMO of LiPF6 (-0.957eV) and the THF solvent (1.851eV) is greater than 1.5eV.

[0059] The pre-lithiated Si-based negative electrode with a rich LiF-SEI film prepared in Example 1 was cut into discs with a diameter of 10 mm as the working electrode (negative electrode sheet), and lithium metal was used as the auxiliary electrode to assemble into a half-cell for current cycling test; the test current was 0.1C, and the cycle was 50 cycles (the button battery itself has a spring to apply pressure, and no additional mechanical pressure is required). The test results showed that the first coulomb efficiency was 92.22%, the 50-cycle charging capacity retention rate was 81.27%, and the 200-cycle charging capacity retention rate was 47.81%.

[0060] Example 2

[0061] The difference between Example 2 and Example 1 is that the components of the fluorine-containing electrolyte are different.

[0062] The concentration of LiPF6 in the fluorine-containing electrolyte of this embodiment is ten times that of the embodiment 1, and a 1M LiPF6 solution is prepared by dissolving LiPF6 in THF solvent. The pre-lithiated Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 1.0M LPF-THF. The energy difference between the LUMO of LiPF6 (-0.957 eV) and the LUMO of THF solvent (1.851 eV) is greater than 1.5 eV.

[0063] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a LiF-SEI-rich film prepared in Example 2 was tested in the manner of Example 1, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 146.91%, the 50-cycle charging capacity retention rate was 69.23%, and the 200-cycle charging capacity retention rate was 34.09%.

[0064] Example 3

[0065] The difference between Example 3 and Example 1 is that the components of the fluorine-containing electrolyte are different.

[0066] In this embodiment, the concentration of LiPF6 in the fluorine-containing electrolyte of this embodiment is twice that of Example 2, and LiPF6 is dissolved in THF solvent to prepare a 2M LiPF6 solution. The pre-lithiated Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 2.0M LPF-THF. The energy difference between the LUMO of LiPF6 (-0.957eV) and the THF solvent (1.851eV) is greater than 1.5eV.

[0067] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a LiF-SEI-rich film prepared in Example 3 was tested in the manner of Example 1, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 107.52%, the 50-cycle charging capacity retention rate was 67.06%, and the 200-cycle charging capacity retention rate was 43.96%.

[0068] Example 4

[0069] The difference between Example 4 and Example 1 is that the components of the fluorine-containing electrolyte are different.

[0070] In this embodiment, the fluorine-containing electrolyte uses electronically pure 1,3-dioxolane (DOL) as a solvent, the solute is LiPF6 powder, and the LiPF6 concentration in the prepared fluorine-containing electrolyte is 0.4M. The pre-lithiated Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 0.4M LPF-DOL. The energy difference between the LUMO of LiPF6 (-0.957eV) and the DOL solvent (1.867eV) is greater than 1.5eV.

[0071] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a LiF-SEI film prepared in Example 4 was tested in the manner of Example 1, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 88.97%, the 50-cycle charging capacity retention rate was 88.02%, and the 200-cycle charging capacity retention rate was 56.19%.

[0072] The ICE of an electrode mainly depends on the ability of lithium ions to embed into the electrode, so generally speaking, low solvation energy and high lithium ion concentration can improve ICE. However, cycling requires the formation of a stable SEI film, so the SEI film components that can promote the formation of non-polar LiF and uniform organic PDOL are the key to balancing ICE and cycling.

[0073] Examples 4-6 are used to compare the effects of different concentrations of DOL solvent on the pre-lithiated Si-based negative electrode.

[0074] Example 5

[0075] The difference between Example 5 and Example 1 is that the components of the fluorine-containing electrolyte are different.

[0076] In this embodiment, the raw material of the fluorine-containing electrolyte solvent is LiPF6, 1,3-dioxolane (DOL) is a solvent, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) is a diluent; the mass proportion of 1,3-dioxolane (DOL) in the fluorine-containing electrolyte is 50%, the mass proportion of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) is 50%, and the concentration of LiPF6 is 0.4M. The pre-lithiation Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 0.4M LPF-DOL (5:5). The energy difference between the LUMO of LiPF6 (-0.957eV) and the DOL solvent (1.867eV) is greater than 1.5eV.

[0077] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a rich LiF-SEI film prepared in Example 5 was tested in the manner of Example 1, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 83.93%, and the 50-cycle charging capacity retention rate was 114.02%. The 50-cycle charging capacity (739.6 mAh / g) was divided by the 1st cycle charging capacity (843.3 mAh / g), and the 50-cycle charging capacity retention rate was 114.02%; the reason why the charging capacity retention rate was greater than 100% was that after 50 cycles, the reversible capacity increased compared with the first cycle; the main reason for the increase in the later specific capacity was that the excessive addition of TTE caused the silicon electrode to not fully exert the initial specific capacity, and then the electrode was activated in the later period, and the specific capacity was improved and stabilized.

[0078] In Example 5, due to excessive diluent, the electrolyte conductivity is reduced, so the ICE is smaller than that of Example 4 and Example 6. When the lithium salt concentration is constant, DOL is the solvent. As the TTE diluent increases, DOL will form a local high concentration (DOL can dissolve lithium salts while TTE cannot dissolve lithium salts, and TTE and Li +The coordination can be basically ignored), which is beneficial to the diffusion of lithium ions (because the number of lithium ions in the high concentration area is greater, and they can be transported in the solvation structure of ion pairs, providing a better ion conduction environment), and improving ICE (Castillo J, Soria-Fernandez A, Sergio Rodriguez-PeaJokinRikarteAdrian Robles-FernandezItziar AldalurRosalia CidJose Antonio Gonzalez-MarcosJavier CarrascoMichel ArmandAlexander SantiagoDaniel Carriazo.Graphene-Based Sulfur Cathodes and Dual Salt-Based Sparingly Solvating Electrolytes: APerfect Marriage for High Performing, Safe, and Long Cycle Life Lithium-SulfurPrototype Batteries[J].Advanced energy materials, 2024, 14(1): 2302378.1-2302378.13. DOI: 10.1002 / aenm.202302378). At the same time, by adding the diluent TTE, a PDOL (poly 1,3-dioxolane) polymer with a high uniform polymerization degree can be constructed on the surface of the Si-based negative electrode.Under the action of lithium salt, 1,3-dioxolane (DOL) and trimethylolpropane triglycidyl ether (TTE) can form poly(DOL-TTE)-LP by ring-opening cross-linking polymerization, which improves the uneven polymerization of DOL in high-concentration electrolyte (Shujing Wen, Chao Luo, Qingrong Wang, Zhenyao Wei, Yanxiang Zeng, Yidong Jiang, Guangxiao Zhang, Hongli Xu, Jun Wang, Chaoyang Wang, Jian Chang, Yonghong Deng, Integrated Design of Ultrathin Crosslinked Network Polymer Electrolytes for Flexible and Stable All-Solid-State Lithium Batteries, Energy Storage Materials, 2022, https: / / doi.org / 10.1016 / j.ensm.2022.02.035). If in pure DOL solvent, the increase of lithium salt concentration will accelerate the ring-opening polymerization of DOL to form uneven organic PDOL, resulting in deterioration of cycle performance). Therefore, adding the diluent TTE can improve the cycle performance to a certain extent, showing that Example 5 is better than Example 6 and Example 4.

[0079] Example 6

[0080] The difference between Example 6 and Example 1 is that the components of the fluorine-containing electrolyte are different.

[0081] In this embodiment, the fluorine-containing electrolyte includes 90% by weight of 1,3-dioxolane (DOL), 10% by weight of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and 0.4M LiPF6. The pre-lithiated Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 0.4M LPF-DOL (9:1). The energy difference between the LUMO of LiPF6 (-0.957 eV) and the DOL solvent (1.867 eV) is greater than 1.5 eV.

[0082] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a rich LiF-SEI film prepared in Example 6 was tested in the manner of Example 1, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 92.38%, and the 50-cycle charging capacity retention rate was 99.91%.

[0083] Example 7

[0084] The difference between Example 7 and Example 1 is that a high-load SiC electrode is used as the negative electrode.

[0085] In this embodiment, the fluorine-containing electrolyte includes a solvent of tetrahydrofuran (THF) of electronic purity or above and LiPF6 at a concentration of 0.1M. The energy difference between the LUMO of LiPF6 (-0.957eV) and the THF solvent (1.851eV) is greater than 1.5eV. The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a rich LiF-SEI film prepared in Example 7 was tested in the manner of Example 1, using a high-load SiC electrode as the negative electrode, the test current was 0.1C, and the cycle was 50 cycles. The test results showed that the first coulomb efficiency was 90.56%, and the 50-cycle charging capacity retention rate was 65.86%.

[0086] Example 8

[0087] The difference between Example 8 and Example 1 is that the components of the electrolyte are different.

[0088] The solvent of the fluorine-containing electrolyte in this embodiment is tetrahydrofuran (THF), and the solute includes 0.5M LiPF6 and 0.1M LiODFB. The energy difference between the LUMO of LiPF6 (-0.957eV), LiODFB (-2.141eV) and THF solvent (1.851eV) is greater than 1.5eV.

[0089] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a LiF-SEI film prepared in Example 8 was tested in the manner of Example 1, with a test current of 0.1C and 200 cycles. The test result was that the first coulombic efficiency was 107.77% (the result is shown in Figure 3 (c) shows that the charge capacity retention rate after 50 cycles is 92.10%, and the charge capacity retention rate after 200 cycles is 80.15%.

[0090] Example 9

[0091] The difference between Example 9 and Example 1 is that the test current density is different.

[0092] In this embodiment, the solvent of the fluorine-containing electrolyte is tetrahydrofuran (THF), and the solute is 0.1 M LiPF6. The energy difference between the LUMO of LiPF6 (-0.957 eV) and the LUMO of THF solvent (1.851 eV) is greater than 1.5 eV.

[0093] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a rich LiF-SEI film prepared in Example 9 was tested with a high current in the manner of Example 1, with the test current being 0.1C for formation, 0.5C for cycle, and 200 cycles. The test results showed that the first coulomb efficiency was 93.08%, the 50-cycle charging capacity retention rate was 69.49%, and the 200-cycle charging capacity retention rate was 56.48%.

[0094] Example 10

[0095] The difference between Example 10 and Example 1 is that the components of the fluorine-containing electrolyte are different.

[0096] In this embodiment, the fluorine-containing electrolyte uses electronically pure 1,3-dioxolane (DOL) as a solvent, the solute is LiPF6 powder, and the LiPF6 concentration in the prepared fluorine-containing electrolyte is 0.6M. The pre-lithiated Si-based negative electrode with a LiF-rich SEI film prepared in this embodiment is recorded as 0.6M LPF-DOL. The energy difference between the LUMO of LiPF6 (-0.957eV) and the DOL solvent (1.867eV) is greater than 1.5eV.

[0097] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a LiF-SEI film prepared in Example 10 was tested in the manner of Example 1, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 138.00%, the 50-cycle charging capacity retention rate was 52.96%, and the 200-cycle charging capacity retention rate was 28.88%.

[0098] Comparing the test results of Example 4 and Example 10, the LiPF6 concentration in Example 10 is higher, the lithium ion diffusion is enhanced, and thus the ICE is improved. However, when the LiPF6 concentration is too high, it will lead to uneven polymerization of DOL, which may cause the formation of an uneven SEI film on the surface of the Si-based negative electrode, so the 50-cycle discharge capacity retention rate is slightly lower after the lithium salt is increased.

[0099] Comparative Example 1

[0100] In this comparative example, the silicon-carbon composite material that has not been pre-lithiated is directly used as the negative electrode of the button battery.

[0101] The half-cell assembled from the non-pre-lithiated Si-based negative electrode slices prepared in this comparative example was tested in the manner of Example 1, without formation, with a test current of 0.1C and 200 cycles. The test results showed that the first coulomb efficiency was 77.39%, the 50-cycle charging capacity retention rate was 74.59%, and the 200-cycle charging capacity retention rate was 42.15%. Figure 3 (a) and (b) are comparative examples 1 (in Figure 3The cycle performance test results of Examples 1-6 and 10 are shown in the figure.

[0102] Comparative Example 2

[0103] The silicon-carbon composite material that has not been pre-lithiated was used as the negative electrode of the button battery, and the assembled half-battery was subjected to high current testing.

[0104] The battery was formed with a current of 0.1C and charged and discharged with a current of 0.5C for 200 cycles. The test results showed that the initial coulomb efficiency was 75.52%, the 50-cycle charging capacity retention rate was 50.14%, and the 200-cycle charging capacity retention rate was 54.77%.

[0105] Comparative Example 3

[0106] The half-cell assembled with the high-load silicon-carbon composite electrode without pre-lithiation as the negative electrode was tested, and the charge and discharge test was carried out at a current of 0.1C for 50 cycles. The test results showed that the first coulomb efficiency was 78.57%, the 50-cycle charging capacity retention rate was 26.32%, and the 200-cycle charging capacity retention rate was 13.51%.

[0107] Comparative Example 4

[0108] The full battery assembled with non-pre-lithiation silicon-carbon composite material as negative electrode and high-voltage lithium cobalt oxide as positive electrode was tested, with 0.02C current formation and 0.1C current charge and discharge test for 50 cycles. The test results showed that the first coulomb efficiency was 44.76%, and the 50-cycle charging capacity retention rate was 20.92%.

[0109] Comparative Example 5

[0110] When assembling button batteries in Comparative Example 5 and Example 1, the pre-lithiated silicon-carbon composite material is used as the negative electrode. The difference is that in Comparative Example 5, high-voltage lithium cobalt oxide is used as the positive electrode.

[0111] In this comparative example, the electrolyte consists of tetrahydrofuran (THF) (solvent) and LiPF6 with a concentration of 0.1M.

[0112] The button battery uses a silicon-carbon composite material as the negative electrode and high-voltage lithium cobalt oxide as the positive electrode. The assembled full battery was tested, formed with a current of 0.02C, and charged and discharged with a current of 0.1C, and cycled 50 times. The test results showed that the first coulomb efficiency was 75.15%, and the 50-cycle charging capacity retention rate was 42.28%.

[0113] Comparative Example 6

[0114] The difference between Comparative Example 6 and Example 1 is that the components of the electrolyte are different.

[0115] In this comparative example, the fluorinated electrolyte contains electronically pure fluoroethylene carbonate (FEC) as solvent and 1M LiPF6 as solute. The energy difference between the LUMO of LiPF6 (-0.957 eV) and the FEC solvent (3.151 eV) is also greater than 1.5 eV.

[0116] The half-cell assembled from the pre-lithiated Si-based negative electrode slices with a rich LiF-SEI film prepared in this comparative example in the manner of Example 1 was tested, with a test current of 0.1C and 50 cycles. The test results showed that the first coulomb efficiency was 113.69%, the 50-cycle charging capacity retention rate was 52.27%, and the 200-cycle charging capacity retention rate was 22.13%; from the test results, it can be seen that although the performance of the electrolyte in this comparative example is improved, the cycle performance decays quickly.

[0117] Verification Example 1

[0118] In Verification Example 1, performance tests and partial characterization tests of the above-mentioned embodiments and comparative examples were carried out.

[0119] The performance test obtained ① discharge specific capacity, ② charge specific capacity, ③ first coulombic efficiency and ④ full battery energy density.

[0120] ① Discharge specific capacity: Cut the prepared negative electrode sheets into circular sheets with a diameter of 10 mm, assemble the circular sheets into 2032 button cells, discharge at a current of 0.1C to a cut-off voltage of 0.01V, record the discharge capacity, and calculate the first discharge specific capacity based on the loading amount of the negative electrode active material.

[0121] ②Charging specific capacity: Charge the fully discharged button battery in A to 2.0V at a current of 0.1C, record the charging capacity, and calculate the first charging specific capacity based on the loading amount of the active material of the negative electrode material.

[0122] ③ First coulombic efficiency: First coulombic efficiency = first charge specific capacity of button cell / first discharge specific capacity × 100%.

[0123] ④ Full battery energy density: The positive electrode sheet, the negative electrode sheet and the separator are assembled into a 2032-type button battery (Comparative Examples 4 and 5 are assembled into a full battery, and the other comparative examples and embodiments are assembled into a full battery), and are formed at a voltage window of 3.0-4.35V according to the conditions of each embodiment and comparative example; Example 9 and Comparative Example 2 are subjected to a large current test, and the other embodiments and comparative examples have a discharge rate of 0.1C. The full battery energy density is calculated based on the third discharge capacity, the discharge platform and the battery weight.

[0124] The test results of the embodiments and comparative examples are shown in Table 1, Table 2 and Figure 3 .

[0125] Table 1 Performance test results of the embodiment

[0126] category First coulombic efficiency 50 cycles charging capacity retention rate 200 cycles charging capacity retention rate Example 1 92.22% 81.27% 47.81% Example 2 146.91% 69.23% 34.09% Example 3 107.52% 67.06% 43.96% Example 4 88.97% 88.02% 56.19% Example 5 83.93% 114.02% - Example 6 92.38% 99.91% - Example 7 90.56% 65.86% - Example 8 107.77% 92.10% 80.15% Example 9 93.08% 69.49% 56.48% Example 10 138.00% 52.96% 28.88%

[0127] Table 2 Performance test results of comparative examples

[0128] category First coulombic efficiency 50 cycles charging capacity retention rate 200 cycles charging capacity retention rate Comparative Example 1 77.39% 74.59% 42.15% Comparative Example 2 75.52% 50.14% 54.77% Comparative Example 3 78.57% 26.32% 13.51% Comparative Example 4 44.76% 20.92% - Comparative Example 5 75.15% 42.28% - Comparative Example 6 113.69% 52.27% 22.13%

[0129] Characterization Tests:

[0130] Surface morphology: The negative electrode without pre-lithiation (denoted as No-P Si / C, the negative electrode composition is the same as the negative electrode in Example 1) and the negative electrode after pre-lithiation with 0.1M LiPF6-THF electrolyte in Example 1 (denoted as 0.1M LPF-THF) were prepared, and the electrode surface morphology was observed by scanning electron microscopy. The results of the negative electrode without pre-lithiation are shown in Figure 4 The negative electrode results after pre-lithiation with 0.1M LiPF6-THF electrolyte in Example 1 are shown in Figure 5 The negative electrode samples after pre-lithiation with 0.1M LiPF6-THF and charge-discharge test after pre-lithiation were analyzed by X-ray photoelectron spectroscopy for SEI components. The results are shown in Figure 6 . Figure 6 (a) is an X-ray photoelectron spectroscopy analysis diagram of the pre-lithiation negative electrode in Example 1 after 10 cycles of charge and discharge testing; (b) is an X-ray photoelectron spectroscopy analysis diagram of the pre-lithiation negative electrode in Example 1.

[0131] The cross-sectional SEM images of the non-pre-lithiated electrode before cycling and after the first discharge / charge are shown in Figure 7 (a), 7(b), 7(c), cross-sectional SEM images of the electrode (pre-lithiated SiC electrode of Example 1) after pre-lithiation with 0.1M LPF-THF electrolyte before cycling and after the first discharge / charge are shown in Figure 7 (d), 7(e), 7(f). Figure 7 It can be seen that pre-lithiation can reduce the volume expansion of the electrode and is beneficial to enhance the cycle stability.

[0132] In addition, the negative electrode without pre-lithiation (No-P Si / C) and the negative electrode in Example 1 (0.1MLPF-THF) were also subjected to nanoindentation tests. Figure 8 It is a load-depth curve; at the same time, the elastic modulus of the electrode without pre-lithiation is 0.853479, and the hardness is 0.023002; the elastic modulus of the electrode after pre-lithiation with 0.1M LPF-THF electrolyte is 1.13044, and the hardness is 0.141765; from the test results, it can be seen that pre-lithiation can improve the mechanical properties of the negative electrode.

[0133] Figure 3In the figure, the SiC electrode without pre-lithiation (Comparative Example 1) and after pre-lithiation with electrolytes of different concentrations and solvents is used as the working electrode, and the metal lithium is used as the auxiliary electrode to assemble the half-cell test to obtain 50 cycles of electrochemical data, the current density is 0.1C, and it is not activated; the parameters of the pre-lithiation electrolyte used are 0.1M LiPF6 dissolved in THF solvent (Example 1), 1.0M LiPF6 dissolved in THF solvent (Example 2), 2.0M LiPF6 dissolved in THF solvent (Example 3), 0.4M LiPF6 dissolved in DOL solvent (Example 4), 0.4M LiPF6 dissolved in a solvent with a DOL:TTE ratio of 5:5 (Example 5), 0.4M LiPF6 dissolved in a solvent with a DOL:TTE ratio of 9:1 (Example 6), and 0.6M LiPF6 dissolved in DOL solvent (Example 10). From Table 1, Table 2, Figure 3 The test results show that after using the pre-lithiation electrolyte proposed in the present invention, a SEI film is formed on the negative electrode surface, which does not consume the positive electrode lithium, so the first coulomb efficiency is greatly improved. For ternary materials, the first coulomb efficiency has been greatly improved. At the same time, during the cycle process, the residual capacity of the battery in each cycle is greatly improved, that is, the cycle life of the battery is extended. Figure 3 It can also be seen from (a) and (b) that the cycle curves of Examples 1 to 6 and 10 are smoother, especially Example 5 (DOL:TTE (5:5)) and Example 6 (DOL:TTE (9:1)), which have slower capacity decay and better cycle performance.

[0134] According to the in-situ polymerization theory, cyclic ether solvents will undergo ring-opening polymerization under the action of lithium salts, forming a more stable polymer in the SEI film (SEI film is a mixed component of organic and inorganic), which can improve the cycle stability of the electrode while taking into account the battery ICE. Only specific lithium salts in the fluorine-containing electrolyte can have a ring-opening polymerization effect on some cyclic ether solvents, such as LiPF6-DOL, LODFB-THF, etc.; while LiPF6-THF and LiPF6-FEC will not have a cyclic solvent opening effect. The LUMO energy difference between ether solvents and lithium salts can make it easier to form inorganic components. Ring-opening polymerization accelerates the closure of electron channels to form a more stable organic component of the SEI film. ICE can also be improved without ring-opening polymerization, but the cycle improvement is not as obvious as ring-opening polymerization. In the present invention, the fluorine-containing electrolyte in Example 1 is 0.1M LiPF6 in THF, without ring-opening polymerization; the fluorine-containing electrolyte in Example 2 is 1M LiPF6 in THF, without ring-opening polymerization; the fluorine-containing electrolyte in Example 4 is 0.4M LiPF6 dissolved in 1,3-dioxolane (DOL), the fluorine-containing electrolyte in Example 5 is 0.4M LiPF6 in 1,3-dioxolane (DOL) with a solvent content of 50%, the fluorine-containing electrolyte in Example 6 is 0.4M LiPF6 in 1,3-dioxolane (DOL) with a solvent content of 90% by mass, and the fluorine-containing electrolyte in Example 10 is 0.6M LiPF6 dissolved in 1,3-dioxolane (DOL), all of which have ring-opening polymerization. Comparison Table 1, Figure 3 From the data in, it can be seen that compared with Example 1 and Example 2, the cycle performance of Examples 4-6 is better.

[0135] Combination Figure 4 , Figure 5 , Figure 6 It can be seen that the electrode surface is smoother after pre-lithiation treatment, which indicates that a high-strength SEI film that can inhibit the volume expansion of the silicon negative electrode is formed on the electrode surface, thereby stably improving the battery cycle performance. Figure 6 The information shows that after ten cycles, the measured F content increased significantly, indicating that more LiF components can be detected on the electrode surface, thereby constructing a LiF-rich SEI film, which is consistent with the expected goal.

[0136] Verification Example 2

[0137] In order to illustrate the cycle performance of button batteries under different assembly conditions, this Verification Example 2 provides the following three groups of pre-lithiation effect comparisons.

[0138] ① The high-load SiC electrode without pre-lithiation and after pre-lithiation with 0.1M LiPF6 and THF as the electrolyte was used as the working electrode, and the half-cell was assembled with metallic lithium as the auxiliary electrode for testing. The charge and discharge test current density was 0.1C and it was not activated. The test results are as follows Fig. 9 As shown in (a), SiC in (a) represents a high-load SiC electrode that has not been pre-lithiated as the working electrode, and 50 cycles of electrochemical data are obtained by assembling a half-cell test with metallic lithium as the negative electrode (Comparative Example 3); 0.1MLiPF6 in (a) represents a high-load SiC electrode that has been pre-lithiated with an electrolyte having a concentration of 0.1M LiPF6 and a solvent of THF as the working electrode, and 50 cycles of electrochemical data are obtained by assembling a half-cell test with metallic lithium as the negative electrode.

[0139] ② is the SiC electrode without pre-lithiation and after pre-lithiation with 0.1M LiPF6 and THF as the solvent. 0.85 Co 0.1 Mn 0.05 The electrochemical data of 50 cycles of full battery (2032 button cell) assembled with O2 material as positive electrode was obtained with current density of 0.1C activation and 0.2C cycle. The test results are as follows Fig. 9 As shown in (b), Si / C||LiNi in (b) 0.85 Co 0.1 Mn 0.05 O2 represents LiNi without pre-lithiation 0.85 Co 0.1 Mn 0.05 50-cycle electrochemical data of full battery test with O2 material as positive electrode, PSi / C||LiNi 0.85 Co 0.1 Mn 0.05 O2 represents the SiC electrode after pre-lithiation with 0.1M LiPF6 and THF as the solvent. 0.85 Co 0.1 Mn 0.05 50-cycle electrochemical data obtained from full battery testing using O2 material as the positive electrode.

[0140] ③ is the electrochemical data of 50 cycles of high current test of SiC electrode without pre-lithiation and after pre-lithiation with electrolyte solution of 0.1M LiPF6 and solvent THF, with lithium metal as negative electrode to assemble half-cell, the current density was 0.1C activation and 0.5C cycle; the test results are as follows Fig. 9As shown in (c), SiC represents 50 cycles of electrochemical data obtained by using a SiC electrode that has not been pre-lithiated as the working electrode and a half-cell assembled with metallic lithium as the negative electrode for a large current test; 0.1M LiPF6 represents 50 cycles of electrochemical data obtained by using a SiC electrode that has been pre-lithiated with an electrolyte solution with a concentration of 0.1M LiPF6 and a solvent of THF as the working electrode and a half-cell assembled with metallic lithium as the negative electrode for a large current test.

[0141] From the above results, it can be seen that no matter under which conditions the test is carried out, the first coulomb efficiency of the SiC electrode after pre-lithiation is improved to varying degrees, especially for the high-nickel ternary positive electrode material LiNi 0.85 Co 0.1 Mn 0.05 When O2 is used as the positive electrode, the first coulombic efficiency is greatly improved. At the same time, during the cycle, the residual capacity of the battery in each cycle is greatly improved, that is, the cycle life of the battery is extended, and there are different performances in different groups, such as Fig. 9 As shown in (a), when a high-load SiC electrode is used as the working electrode, there is no obvious decrease in the residual capacity of the pretreated SiC electrode after 20 cycles; Fig. 9 As shown in (b), in LiNi 0.85 Co 0.1 Mn 0.05 When O2 is used as the positive electrode, the residual capacity of the full battery composed of pre-lithiated SiC electrodes is more stable than that of the non-pre-lithiated treatment; Fig. 9 As shown in (c), before about 120 cycles, the pre-lithiation SiC electrode has obvious excellent performance in the high current test. After that, the difference between the pre-lithiation and non-pre-lithiation treatments decreases.

[0142] The present invention compares the electrochemical performance of fluorine-containing lithium salts in electrolytes prepared with lipid and ether solvents. Among electrolyte solvents, lipids have lower LUMO energy than ethers, which will cause the lipid solvent and fluorine-containing lithium salt to decompose simultaneously, reduce the amount of LiF in the SEI film, and thus lead to worse battery cycle performance. In addition, ether solvents have lower binding energy, which is also conducive to improving the transmission efficiency of lithium ions during the pre-lithiation process and improving the first coulombic efficiency of the battery.

[0143] The improvement of pre-lithiation and cycle performance increases first and then decreases with the concentration of fluorinated lithium salt in the ether electrolyte. As can be seen from Examples 1-3, the first coulombic efficiency (ICE) increases first and then decreases with the increase of concentration, indicating that the increase in the initial fluorinated lithium salt concentration provides a large amount of Li + and F source, making the ion transport channel efficiency faster during the pre-lithiation process, but as the concentration of fluorinated lithium salt increases, the viscosity of the electrolyte increases, and Li + The effective radius or transmission mechanism of Li+ The difficulty coefficient of F source movement is increased exponentially, resulting in a reduction in the improvement effect.

[0144] In summary, the electrolyte system proposed in the present invention, after being applied to the pre-lithiation of electrode sheets, the obtained electrode sheets are assembled into batteries for charge and discharge tests, which can greatly improve the initial efficiency and cycle performance of lithium-ion batteries.

[0145] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.

Claims

1. A roll-to-roll continuous method for preparing a pre-lithiated Si-based negative electrode having a LiF-SEI-rich film, characterized in that: The following steps are involved: (1) spraying a fluorine-containing electrolyte on the upper and lower surfaces of a Si-based negative electrode strip (100) so that the fluorine-containing electrolyte can evenly infiltrate the electrode pores; the fluorine-containing electrolyte comprises a cyclic ether solvent and a fluorine-containing lithium salt, and the energy difference between the LUMO of the fluorine-containing lithium salt and the cyclic ether solvent is greater than 1.5 eV; (2) pulling two ultra-thin lithium strips (200) and a Si-based negative electrode strip (100) sprayed with a fluorine-containing electrolyte on both sides through a roll-to-roll pre-lithiation device (2); the two ultra-thin lithium strips (200) are respectively located on the upper and lower sides of the Si-based negative electrode strip (100), and the three are rolled through the roll-to-roll pre-lithiation device (2); after lithium ions are released from the ultra-thin lithium strips (200), they are embedded in the Si-based negative electrode strip (100) through the electrolyte, and the electrochemical potential of the Si-based negative electrode strip (100) decreases as the amount of embedded lithium increases, and the electrolyte is spontaneously reduced and decomposed on its surface to form an SEI film; (3) removing the ultra-thin lithium strips (200) on both sides of the Si-based negative electrode strip (100), drying the Si-based negative electrode strip (100), and obtaining a pre-lithiated Si-based negative electrode having a LiF-SEI-rich film.

2. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: The cyclic ether solvent includes at least one of 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and methyltetrahydrofuran; the fluorine-containing lithium salt includes one or more of LiPF6, LiTFSI, LiPO2F2, LiFSI, and LiODFB.

3. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: Other solvents of the fluorine-containing electrolyte include diluents or film-forming additives.

4. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: In the fluorine-containing electrolyte, the concentration of the fluorine-containing lithium salt is 0.1-2 mol / L.

5. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: In step (1), the amount of fluorine-containing electrolyte sprayed on the Si-based negative electrode tape (100) is 500-2000 ml / m 2 , the spraying temperature is 10-30℃, and the environment is a water-free environment.

6. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: In step (2), the speed at which the ultra-thin lithium strip (200) and the Si-based negative electrode strip (100) pass through the roll-to-roll pre-lithiation device (2) is 1-5 cm / s; the rolling temperature of the roll-to-roll pre-lithiation device (2) during the rolling process is 10-30° C., the number of rolling times is 1-3 times, the rolling pressure is 10-100 KPa, and the relative humidity of the rolling environment is 10%-30%.

7. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-rich SEI film according to claim 1, characterized in that: In step (3), the drying temperature of the Si-based negative electrode strip (100) is 50-60°C, and the drying time is 0.5-2h; the used ultra-thin lithium strip (200) is polished, cut, crushed, squeezed, thinned and rolled by the lithium metal recovery device (4) to expose the fresh surface for secondary utilization.

8. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: The Si-based negative electrode strip (100) is a silicon-carbon composite material or a silicon-oxygen-carbon composite material; the surface capacity of the Si-based negative electrode strip (100) is 2-5 mAh / cm 2 , with a thickness of 50-250 μm; the ultra-thin lithium strip (200) has a thickness of 5-20 μm and is loaded on the surface of the copper strip.

9. The method for roll-to-roll continuous preparation of a pre-lithiated Si-based negative electrode having a LiF-SEI rich film according to claim 1, characterized in that: The SEI film thickness of the pre-lithiated Si-based negative electrode having a LiF-rich SEI film is 10-100 nm.